Empathy and nausea: virtual reality and Jordan Wolfson's Real Violence. (April 2020) - Bollmer, Grant; Guinness, Katherine
Jordan Wolfson's Real Violence (2017) is a brief virtual reality (VR) piece that depicts the artist beating a man to death with a baseball bat. Wolfson uses the haptic possibilities of VR to rapidly induce nausea in the viewer, an act that both relies on empathetic aspects of VR simulation – 'empathy' here linked with its history in German aesthetic psychology as Einfühlung – and is a confrontational distancing that questions the politics of 'empathetic' immersion. Real Violence demonstrates how contemporary judgments of VR and empathy repeat debates from the late 19th and early 20th centuries, reinventing and emptying particular political/aesthetic strategies that have long characterized a strain of modernist art that uses the formal possibilities (and limits) of media in order to critique the very same possibilities (and limits). This article, through its discussion of Wolfson's work, seeks to identify and inhabit the complex contradictions present in any discussion of empathy, transgressive confrontation, and the social function of art and VR today. It examines the limitations of immersion and emotional projection, along with the limitations of interpreting this work (and VR in general) as a means for enacting 'progressive' social and ideological change through the immersive, empathetic capacities of media. The article concludes by arguing that judgments of Real Violence (and the politics of 'transgressive' art more broadly) require assuming the will or intent of an artist who uses confrontation and transgression to 'correct' the experience of the viewer, which is something that cannot be assumed for either Wolfson or Real Violence, and rather his work is exemplary of emptying out the possibilities represented by both VR and critical aesthetic intervention.